IDENTIFICATION EXPERTISE OF TOOTHPASTE - SIRENKO, SVITLANA; VLASENKO, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The modern domestic market of cosmetics is characterized by a large number of counterfeit products that do not meet the requirements of quality and safety. To identify counterfeit cosmetics (toothpastes), their identification examination was carried out. Statistical data show that among other groups of goods, cosmetic products, which are potentially harmful, are the most counterfeited. The problems of establishing the authenticity, identification, and safety of cosmetic products are one of the main tasks facing experts and trade representatives, which makes this study relevant. The article substantiates the need for systematic identification of ecological toothpastes. An algorithm for their identification and criteria, means and methods for its implementation are proposed. The following criteria were used as identification criteria: information content (manufacturer, name), organoleptic indicators (color, consistency, taste, mass, condition, tube packaging, smell), physicochemical indicators (hydrogen Ph, mass fraction of water, foaming ability, mass of paste in the tube, mass fraction of fluoride. It was found that some samples have deviations from the labeling requirements. Timely and correctly carried out identification examination will allow to identify and eliminate poor-quality and unsuitable cosmetic dental products on the way to the consumer. The identification examination of toothpastes showed that they meet the requirements of the standard in terms of organoleptic and physico-chemical indicators. The identification marking of toothpastes showed that there are deviations from the standard values ​in some toothpaste samples for certain marking details.